GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 233 species occurrences available in GBIF matching the query: TaxonKey: Pitcairnia atrorubens (Beer) Baker. The dataset includes 233 records from 17 constituent datasets: 5 records from Herbarium Senckenbergianum (FR). 78 records from Missouri Botanical Garden. 32 records from herbario. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 5 records from University of Vienna, Institute for Botany - Herbarium WU. 4 records from Geographically tagged INSDC sequences. 2 records from Field Museum of Natural History (Botany) Seed Plant Collection. 3 records from Colección Herbario Federico Medem Bogotá - FMB. 1 records from Wilson Botanical Garden - Las Cruces Biological Station. 1 records from UCD BOTANICAL CONSERVATORY. 15 records from Instituto de Ciencias Naturales. 2 records from Instituto de ciencias naturales. 1 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from Digital Florula - Las Cruces Biological Station. 2 records from SysTax - Botanical Gardens. 4 records from CAS Botany (BOT). 76 records from Especímenes INBio.
Keywords: GBIF; biodiversity; species occurrences